(Un)organizing equal collaboration between users and professionals: on management of patient education in Norway. (30th May 2011) - Stokken, Roar
Abstract Background This is an article about how patient education is managed in Norway, but it also addresses a matter of broader relevance that of how an organization imbued with a request for rational choices is able to take on board a contradictory ideology. In Norway, patient education under the auspice of hospitals is to be conducted as an equal collaboration between users and professionals, posing challenges to the ethos of rationally justified choices within the hospital sector. This calls for an exploration of how the organization copes with the contradictory demands. Methods A theoretical approach on the basis of theories from Scandinavian institutional theory and science and technology studies, informed by documents, interviews and experiences from national, regional and local levels in Norway. Discussion The field of patient education is divided into three decoupled domains: one at management level, one at the practical level, and in the middle a domain that acts as an interface between management and practice. This interface mediates the relationship between ideas and practice, without making overt the fact that ideas might not be possible to put into practice and that practice might not reflect ideas. Conclusions The decoupling of practice and management allows patient education as equal collaboration between users and professionals to thrive as an idea, not subjugated by practical challenges. Thus, it can exist as a guiding star that both management and practitioners can attune to, but this situation might now be threatened by the demand for quality assurance in the field.